Design and Realization of Smart Plug Based On QR Code and WIFI Access - Gistya Sudiartama, Annenta; Darlis, Denny; Hartaman, Aris (Greenation Research & Yayasan Global Resarch National, 2023)
The traditional electrical outlet has evolved with the emergence of